1993
DOI: 10.1139/f93-230
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Sulfur, Carbon, and Nitrogen in Tissue of Growing Broad Whitefish (Coregonus nasus) in Response to a Change in Diet Traced by δ34S, δ13C, and δ15N

Abstract: We monitored the change in the isotope composition of sulfur, carbon, and nitrogen in broad whitefish (Coregonus nasus) tissues in response to a change in the isotope composition of their food. One of two batches of 2.5-yr-old fish raised in the laboratory were given a new food source with different δ34S, δ13C, and δ15N, which were monitored in muscle and liver tissue for 1 yr. A model including change due to tissue accumulation (growth) and metabolic replacement was developed. For all three isotopes, most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
749
8
17

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(816 citation statements)
references
References 6 publications
29
749
8
17
Order By: Relevance
“…After the experimental dietary treatments were differentiated, shifts in δ 13 C values of shrimp fed on the different feeding regimes (except those fed on inert diet) stabilized quickly in the mysis and postlarval stages. Rapid isotopic changes are due to both, high growth and metabolic turnover rates, in the present study indicated by parameters from the exponential model (Hesslein et al, 1993). Fry and Arnold (1982) also observed fast δ 13 C turnover in P. aztecus shrimp postlarvae fed Artemia, which led to short carbon metabolic half time in tissue (4 d).…”
Section: Influence Of Diet On Isotope Value Changes and Carbon Turnovsupporting
confidence: 75%
See 1 more Smart Citation
“…After the experimental dietary treatments were differentiated, shifts in δ 13 C values of shrimp fed on the different feeding regimes (except those fed on inert diet) stabilized quickly in the mysis and postlarval stages. Rapid isotopic changes are due to both, high growth and metabolic turnover rates, in the present study indicated by parameters from the exponential model (Hesslein et al, 1993). Fry and Arnold (1982) also observed fast δ 13 C turnover in P. aztecus shrimp postlarvae fed Artemia, which led to short carbon metabolic half time in tissue (4 d).…”
Section: Influence Of Diet On Isotope Value Changes and Carbon Turnovsupporting
confidence: 75%
“…In order to obtain an estimate of the metabolic carbon turnover rate, changes in δ 13 C values in shrimp following a dietary shift from C. gracilis to the different experimental feeding regimes were fitted to the following exponential model (Hesslein et al, 1993) in order to integrate growth and isotope value shift over time:…”
Section: Estimation Of Carbon Turnover Ratesmentioning
confidence: 99%
“…Total dry matter contributions were estimated after correcting for nitrogen concentrations measured in both ingredients using the equation proposed by Fry (2006). δ 15 N values measured through the experimental period were integrated in an exponential model of isotopic change (Hesslein et al, 1993) to obtain an estimate of the metabolic nitrogen turnover rate in shrimp muscle tissue. The model allows distinguishing the isotopic change that is due to growth (k) or metabolic turnover (m).…”
Section: Estimation Of Nutrient Contribution and Nitrogen Half Lives mentioning
confidence: 99%
“…The use of stable carbon and nitrogen isotope ratios (expressed as d 13 C and d 15 N, respectively) in studies of fish diets and lake food-web structure is based on the distinct d 13 C values of pelagic and littoral primary producers and on the trophic enrichment of d 15 N by around 3-4& per trophic level . The d 13 C and d 15 N values from fish muscle tissue typically reflect the diet assimilated over a few months (Hesslein, Hallard & Ramlal, 1993;. Hence, isotopic studies of fish trophic ecology are not subject to the same potential sampling errors as SCA, such as temporal changes in availability, patchy distribution and different digestion times of prey items Boecklen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The observed partial reliance of pelagic-caught planktivorous charr on littoral carbon sources may reflect general niche plasticity and ⁄ or consumption of pleuston originating from the littoral or profundal zone that has a higher d 13 C value than the predominant zooplankton diet. Because of the long turnover time of muscle tissue (Hesslein et al, 1993;, the isotopic composition of pelagic-caught charr may also partly reflect their spring-time diet, which is likely to have been dominated by littoral zoobenthos at a time when zooplankton is extremely sparse in these lakes .…”
mentioning
confidence: 99%